Mechanisms of Complete Dissociation of CO2 on Iron Clusters. Issue 21 (3rd August 2022) - Gutsev, Gennady L.; Tibbetts, Katharine M.; Gutsev, Lavrenty G.; Aldoshin, Sergey M.; Ramachandran, Bala R.
Abstract: Dissociation of CO2 on iron clusters was studied by using semilocal density functional theory and basis sets of triple‐zeta quality. Fe2, Fe4, and Fe16 clusters were selected as the representative host clusters. When searching for isomers of Fe n CO2, n =2, 4 and 16 corresponding to carbon dioxide attachment to the host clusters, its reduction to O and CO, and to the complete dissociation, it was found that the total spin magnetic moments of the lowest energy states of the isomers are often quenched with respect to those of initial reagents Fe n +CO2 . Dissociation pathways of the Fe2 +CO2, Fe4 +CO2, and Fe16 +CO2 reactions contain several transition states separated by the local minima states; therefore, a natural question is where do the spin flips occur? Since lifetimes of magnetically excited states were shown to be of the order of 100 fs, the search for the CO2 dissociation pathways was performed under the assumption that magnetic deexcitation may occur at the intermediate local minima. Two dissociation pathways were obtained for each Fe n +CO2 reaction using the gradient‐based methods. It was found that the Fe2 +CO2 reaction is endothermic with respect to both reduction and complete dissociation of CO2, whereas the Fe4 +CO2 and Fe16 +CO2 reactions are exothermic to both reduction and complete dissociation of carbon dioxide. The CO2 reduction was found to be more favorable than its complete dissociation in the Fe4 case. Abstract : CO2 dissociation on Fe2, Fe4, and Fe16 clusters is studied by using semilocal density functional theory. Several dissociative pathways are explored with the assumption that the spin magnetic moments might be quenched in the dissociation process.